2020
DOI: 10.3389/fpsyg.2020.01608
|View full text |Cite
|
Sign up to set email alerts
|

Positivity Ratio and Well-Being Among Teachers. The Mediating Role of Work Engagement

Abstract: Previous studies indicated that the balance of positive to negative affect (i.e., positivity ratio) is associated with subjective well-being and flourishing in the general population. Moreover, a positivity ratio of 2.9 is considered a critical value discriminating between flourishing and non-flourishing individuals. To date, however, there is limited research on the positivity ratio on samples of teachers. The present study aimed to investigate whether the positivity ratio affects work engagement and well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 79 publications
3
30
0
2
Order By: Relevance
“…With the rise of optimistic psychology in the research community, new ways of discussing discussions on teacher well-being are circulating [14], [15]. Teacher well-being has gained a lot of interest over the past few decades [16], [17] states that the positive ratio (ratio between positive and negative emotions) experienced by teachers will increase their work engagement, which in turn will positively affect well-being them. Many scholars found that personal resources (self-esteem, optimism, self-efficacy, and active coping) have been positively related to work engagement and psychological well-being and negatively associated with exhaustion [18], [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rise of optimistic psychology in the research community, new ways of discussing discussions on teacher well-being are circulating [14], [15]. Teacher well-being has gained a lot of interest over the past few decades [16], [17] states that the positive ratio (ratio between positive and negative emotions) experienced by teachers will increase their work engagement, which in turn will positively affect well-being them. Many scholars found that personal resources (self-esteem, optimism, self-efficacy, and active coping) have been positively related to work engagement and psychological well-being and negatively associated with exhaustion [18], [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nurses' subjective well-being is very important for both individuals and organizations, as it helps increase job stability and satisfaction [48]. In many studies on subjective wellbeing, work engagement was found to be an intermediary factor [49], which meant that an increasing level of work engagement could indirectly improve an individual's subjective well-being. Subjective wellbeing was found to be moderately related to work engagement among Polish individuals [50].…”
Section: Discussionmentioning
confidence: 99%
“…Professionally engaged employees are engrossed in and focused on their jobs and tend to increase their commitment to their jobs over time (Schaufeli et al, 2002). The topic of professional engagement has been widely researched in the field of education (Kozikoglu & Senemoglu, 2018;Rusu & Colomeischi, 2020). The teaching profession requires content knowledge and specific competencies, as well as competencies related to positive human relationships and problem-solving.…”
Section: Highlightsmentioning
confidence: 99%
“…Teachers who are dedicated to fulfilling the requirements of their profession and who focus on the work they do are evaluated in the context of professional engagement (Granziera & Perera, 2019). Psychological well-being is also a predictor of professional engagement (Rusu & Colomeischi, 2020;Shimazu et al, 2012) as teachers with high levels of professional engagement perform their jobs at a higher level (Spilt et al, 2011).…”
Section: Highlightsmentioning
confidence: 99%